PENANAMAN NILAI MORAL ANAK DI LINGKUNGAN LOKALISASI (STUDI KASUS TPQ AR-RAHMAN KALIBANTENG KULON KOTA SEMARANG) - Maulana Arif Setyawan (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
TPQ Ar-Rahman is religious institutions that handles education and guidance for children who live in the Sunan Kuning localization environment. Sunan Kuning is an area for Commercial Sex Workers in Semarang. The existence of Commercial Sex Workers in Sunan Kuning certainly has a negative impact on the development of children who live around the localization environment. This research is a descriptive-qualitative study in which the type of research used is case study research. The result of this study indicates that the inculcation of moral values ​​in children aims to direct them to live according to the religious norms and morality. The inculcation of moral values ​​in children in the TPQ Ar-Rahman is very beneficial for students in particularly and for all elements of society in generally. The role of teachers, parents, and the environment is also very important in order to shape the child's personality based on the Islamic teachings.